Unlocking the potential of cyclic peptides in bioactive wound dressings for enhanced tissue repair - S. Muthukumar; S. Monic Josephine Nithila; Laliteshwar Pratap Singh; M. Akiful Haque; Swathy Govindaswamy; Srinivas Murthy BR (Molecular Biology Reports, 2026)

Spatial heterogeneity of microplastic pollution and associated emerging contaminants in tropical estuarine environments: Novel insights into distribution, bioavailability, and ecological risk - Vijayalekshmi Padmachandran Aiswriya; P.S. Nishmitha; Kochuparambil Ajayaghosh Akhilghosh; Karunakaran Malavika; Swathy Krishna; Muthukumar Muthuchamy; S. Krishnakumar; Anbazhagi Muthukumar (Marine Pollution Bulletin, 2026)

Anti-Obesity Effect of Probiotic Carrot Nectar Incorporated with L. Plantarum MCC5231 - Aditi Goel; Md Touseef Khan; S. P. Muthukumar; Attar Singh Chauhan; Jyoti Prakash Tamang; Prakash. M. Halami (Probiotics and Antimicrobial Proteins, 2026)

Well-designed construction of rare earth ruddlesden-popper oxide confined on reduced graphene oxide nanosheets: A promising electrocatalyst for the monitoring of anthropogenic toxin - Santhiyagu Sahayaraj Rex Shanlee; Muthukumar Govindaraj; Tse-Wei Chen; Shen ming-chen; Arockia Selvi J; Pichai Christina Ruby Stella; Safaa S. Taha; Mohamed Farouk Elsadek; Mohamed S. E. (Process Safety and Environmental Protection, 2026)

Prevalence of emerging contaminants in the outlet of sewage treatment plants: an evidential report from Kerala, India with future concerns - Kochuparambil Ajayaghosh Akhilghosh; Athira Ramesh; Vijayalekshmi Padmachandran Aiswriya; Salman Farissi; P. S. Nishmitha; C. T. Aravindakumar; M. Thalamadai Karuppiah; Muthukumar Muthuchamy; Anbazhagi Muthukumar (Environmental Sustainability, 2026)

Valorization of biomacromolecular algae oil via nanoparticle-enriched blends for eco-friendly fuel performance - Ali El-Rayyes; Hassen Sabeur; S. Dhivya; K. Muthukumar; Muneera Altayeb; Ankur Bahl; A.Anderson (Fuel, 2026)

Biodegradation pathway and mechanism of new emerging pollutants neonicotinoids - Azhagarsamy Satheeshkumar; Ramanathan Duraimurugan; Premalakshmi Velu; Balakrishnan Muthukumar; Selvakumar Santhosh; Sandhanasamy Devanesan; Mohamad S. AlSalhi; Kuppusamy Sathishkumar; Pattanathu KSM Rahman; Aruliah Rajasekar (Journal of Environmental Sciences, 2026)

A critical review on technical advances and multifaceted role of carotenoids in human health with special emphasis on metabolic diseases - Sayani Roy; K. C. Dora; Siddhnath Kumar; Pooja Saklani; A. Muthukumar; Fatih Ozogul; K. C. Harisankar; R. D. Mutum; S. Celine Hilda Mary; V. K. R. Surasani; P. K. Dara (Phytochemistry Reviews, 2026)

Peptide Epitope-Based Avian IgY Antibodies against SARS-CoV-2 Spike: A Cost Effective Approach for Viral Detection and Neutralization - G. N. Pramod; Prasan Havlad; Nalina Murthy; Abdul Majid; Jessie Thomas; M. Ghalib Enayathullah; Yogesh Sardana; P. K. Sreeram; S. P. Muthukumar; Tanaji Kudre; Pananghat Gayathri; Kiran Kumar Bokara; et al. (International Journal of Peptide Research and Therapeutics, 2025)

Biosensing and Biotechnological Applications of Nanofillers: Current Status and Perspectives - Muthukumar Raghunathan; Ashish Kapoor; Praveen Kumar; S. C. Tripathi; Shafiul Haque; Dan Bahadur Pal (Indian Journal of Microbiology, 2025)

Molecularly Imprinted Polymers Coupled with Cellulosic Paper-Based Analytical Devices for Biosensing Applications - Ashish Kapoor; Muthukumar Raghunathan; Praveen Kumar; S. C. Tripathi; Shafiul Haque; Dan Bahadur Pal (Indian Journal of Microbiology, 2025)

Retraction Note: Structural characterization of Bacillus licheniformis Dahb1 exopolysaccharide—antimicrobial potential and larvicidal activity on malaria and Zika virus mosquito vectors - Muthukumar Abinaya; Baskaralingam Vaseeharan; Mani Divya; Sekar Vijayakumar; Marimuthu Govindarajan; Naiyf S. Alharbi; Jamal M. Khaled; Mohammed N. Al-anbr; Giovanni Benelli (Environmental Science and Pollution Research, 2025)

Recurrent Swarms of Planktonic Shrimp Luciferidae De Haan, 1849 (Order: Decapoda) in the Neritic Waters of Tamil Nadu, Southeast Coast of India - R. S. Sathishkumar; B. Charan Kumar; C. Muthukumar; N. Logesh; Sanitha K. Sivadas; K. Ramu; M. V. Ramana Murthy (Marine Ecology, 2024)
Luciferidae (Decapoda) are an important component of mesozooplankton in pelagic food webs. This study investigated the spatiotemporal distribution and frequency of Luciferidae swarms along the Tamil Nadu coast, as observed during coastal monitoring cruises conducted between 2019 and 2022. Data were collected on various hydrobiological factors, including surface water temperature, salinity, chlorophyll a , zooplankton biomass, and the abundance of other mesozooplankton (such as copepods, cladocerans, and others) across eight locations in the coastal waters of Tamil Nadu, India. Salinity values were generally low ( Belzebub hanseni Nobili, 1905, as the only organism responsible for swarm formation, with its occurrence peaking in January 2022. During this period, B. hanseni reached a maximum abundance of 3294 ind. m −3 for adults and 4056 ind. m −3 for larvae, together contributing approximately 27% of the total zooplankton abundance. Swarms of B. hanseni were observed a total of seven times over the course of the study, correlating with periods of low sea surface temperature and high food availability. Pearson's correlation analysis revealed a significant relationship between the abundance of copepods and B. hanseni ( r = 0.84; p B. hanseni in the nearshore waters of the Tamil Nadu coast is largely driven by food availability and optimal environmental conditions, including water temperature and monsoonal influences. The findings also suggest that geographical features, such as mangrove habitats, may contribute to the occurrence of B. hanseni swarms in this region.

Microplastics in water from the Cooum River, Chennai, India: An assessment of their distribution, composition, and environmental impact - J. Mohamed Afzal; S. Selvam; P. Saravanan; Priyadarsi D. Roy; P. Sanju; P. Muthukumar (Groundwater for Sustainable Development, 2024)

Engineering the functionality of porous organic polymers (POPs) for metal/cocatalyst-free CO2 fixation at atmospheric conditions - Rajesh Das; Ram Kishan; D. Muthukumar; Renjith S. Pillai; C.M. Nagaraja (Journal of Environmental Chemical Engineering, 2024)

Identification of groundwater potential zones of Alappuzha (Kerala) in South India integrating AHP and GIS - Selvam Sekar; Akhila V. Nath; Priyadarsi Debajyoti Roy; Sang Yong Chung; Hussam Eldin Elzain; Paula C. S. Carvalho; Muthukumar Perumal (Environment, Development and Sustainability, 2024)

Distribution and Characterization of Microplastics Along the Coastal Shoreline of Thiruvananthapuram District, Kerala, India - H. S. Arjun; Vijayalekshmi Padmachandran Aiswriya; Muthukumar Muthuchamy; S. Krishnakumar; Satheesh Herbert Singh; Anbazhagi Muthukumar (Water, Air, & Soil Pollution, 2024)

Integrated approach of nano assisted biodegradation of anthracene by Pseudomonas aeruginosa and iron oxide nanoparticles - Balakrishnan Muthukumar; Azhagarsamy Satheeshkumar; Punniyakotti Parthipan; Bibek Laishram; Ramanathan Duraimurugan; Sandhanasamy Devanesan; Mohamad S. AlSalhi; Rajaram Rajamohan; Aruliah Rajasekar (Environmental Research, 2024)

Bisphenol A contamination in processed food samples: an overview - P. Kumar; R. S. Aruna Priyanka; P. Shalini Priya; B. Gunasree; S. Srivanth; S. Jayasakthi; A. Kapoor; R. MuthuKumar (International Journal of Environmental Science and Technology, 2023)

Screening and validation of Ty-1, Ty-3 and Ty-3a specific markers in Solanum chilense accessions for resistance to tomato leaf curl virus - Muthukumar Palanisamy; Gograj Singh Jat; Pritam Kalia; Chitra Devi Pandey; Selvakumar Raman; Shilpi Kumari; Sachin Kumar; B. S. Tomar (Genetic Resources and Crop Evolution, 2023)

Evaluation of groundwater for nitrate and fluoride in Alappuzha region from the southwestern coast of India and associated health risks - S. Selvam; Akhila V. Nath; Priyadarsi D. Roy; K. Jesuraja; P. Muthukumar (Environmental Research, 2023)

Undrained response of fibre reinforced expansive soil subjected to cyclic loading - S. Reehana; M. Muthukumar (Soil Dynamics and Earthquake Engineering, 2023)

Using structure-from-motion to estimate cover crop biomass and characterize canopy structure - April M. Dobbs; Daniel Ginn; Søren Kelstrup Skovsen; Ramawatar Yadav; Prashant Jha; Muthukumar V. Bagavathiannan; Steven B. Mirsky; Chris S. Reberg-Horton; Ramon G. Leon (Field Crops Research, 2023)

Corrigendum to addresses “Effective biocontrol of banana fusarium wilt tropical race 4 by a bacillus rhizobacteria strain with antagonistic secondary metabolites” [Rhizosphere 18 (2021) 100341] - Kavita Yadav; T. Damodaran; Kakoli Dutt; Arjun Singh; M. Muthukumar; S. Rajan; Ram Gopal; P.C. Sharma (Rhizosphere, 2023)

Assessment of phytoplankton diversity, distribution, and environmental variables along the southeast coast of India - P. Sathish Kumar; G. Dharani; J. Santhanakumar; Dilip Kumar Jha; Vikas Pandey; S. Venkatnarayanan; J. Prince Prakash Jebakumar; C. Muthukumar; R. Arthur James (Frontiers in Marine Science, 2023)
Coastal waters are dynamic because of anthropogenic activities that contribute nutrients and contaminants. These changes have the potential to alter patterns of primary production and thus pelagic food webs. Here, we investigated the spatial variation of the phytoplankton community and its response to changing environmental variables at 84 stations along the five coastal districts of Tamil Nadu (TN). During the present study, 85 phytoplankton species were recorded, such as diatoms (64), dinoflagellates (18), silicoflagellates (1), and Cyanophyceae (2). The maximum phytoplankton abundance was recorded on the Thanjavur coast and gradually decreased towards the south coast of Tamil Nadu. Among the phytoplankton community, 50% was dominated by pennate diatoms, attributed to higher NO 3 − concentrations in the coastal waters due to agricultural discharge. Cluster analysis revealed that Ramanathapuram and Tirunelveli formed a closed cluster, whereas Thanjavur and Pudukottai formed a separate closed cluster associated with higher nutrient and metal concentrations, highlighting the difference in physicochemical parameters between the northern and southern districts of the TN coast. Relatively high nutrient concentrations in the coastal waters of northern districts are of greater concern, which could impact the coastal ecosystem. Coastal eutrophication is becoming a widespread phenomenon, causing disruption in the food chain and ecosystem balances and hence requiring regular monitoring and management.

Impact of microfiber pollution on aquatic biota: A critical analysis of effects and preventive measures - K.K. Priya; H. Thilagam; T. Muthukumar; S. Gopalakrishnan; Muthusamy Govarthanan (Science of The Total Environment, 2023)

Submarine groundwater discharge: An Asian overview - Sruthy Sajeev; P. Muthukumar; S. Selvam (Chemosphere, 2023)

Thermal performance and emission analysis of self-aspirated kerosene pressure stove with porous radiant burner using kerosene nanofuels - G. S. Sinha; N. Kumar Mishra; P. Muthukumar; M. Sharma (International Journal of Environmental Science and Technology, 2023)

Strain Identification and Herbivore–Host Interaction of Maize Hosting Invasive Alien Pest Spodoptera frugiperda under Elevated Temperature and CO2 Levels - K. Ashok; V. Balasubramani; M. Muthukumar; J. S. Kennedy; V. Geethalakshmi; N. Sathiah (Agricultural Research, 2023)

Multifarious extraction methodologies for ameliorating lipid recovery from algae - Mohapatra Sneha; S. Sowmya; M. Premalatha; Krishnamurthy Mathivanan; Krishnan Muthukumar; Thangavel Mathimani (Environmental Research, 2023)

Influence of bioaugmentation in crude oil contaminated soil by Pseudomonas species on the removal of total petroleum hydrocarbon - Balakrishnan Muthukumar; Saravanan Surya; Krithiga Sivakumar; Mohamad S. AlSalhi; Tentu Nageswara Rao; Sandhanasamy Devanesan; Paulraj Arunkumar; Aruliah Rajasekar (Chemosphere, 2023)

Synthesis of silver nanoparticles from Indian red yeast rice and its inhibition of biofilm in copper metal in cooling water environment - Muthukumar Suganya; Parameswaran Sujatha Preethi; Jayaraman Narenkumar; Arumugam Arul Prakash; Sandhanasamy Devanesan; Mohamad S. AlSalhi; Aruliah Rajasekar; Ayyakkannu Usha Raja Nanthini (Environmental Science and Pollution Research, 2022)

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

Geomorphology and Landslide Proneness of Kerala, India A Geospatial study - SM. Ramasamy; S. Gunasekaran; J. Saravanavel; R. Melwyn Joshua; R. Rajaperumal; R. Kathiravan; K. Palanivel; M. Muthukumar (Landslides, 2021)

Socio-ecological studies on a tropical coastal area in southern India - M. S. Gokul; H.-U. Dahms; S. Henciya; T. Dhineshkumar; K. Muthukumar; R. A. James (International Journal of Environmental Science and Technology, 2019)

RETRACTED ARTICLE: Structural characterization of Bacillus licheniformis Dahb1 exopolysaccharide—antimicrobial potential and larvicidal activity on malaria and Zika virus mosquito vectors - Muthukumar Abinaya; Baskaralingam Vaseeharan; Mani Divya; Sekar Vijayakumar; Marimuthu Govindarajan; Naiyf S. Alharbi; Jamal M. Khaled; Mohammed N. Al-anbr; Giovanni Benelli (Environmental Science and Pollution Research, 2018)

An enhancement of antimicrobial efficacy of biogenic and ceftriaxone-conjugated silver nanoparticles: green approach - Rajasree Shanmuganathan; Davoodbasha MubarakAli; Desika Prabakar; Harshiny Muthukumar; Nooruddin Thajuddin; Smita S. Kumar; Arivalagan Pugazhendhi (Environmental Science and Pollution Research, 2018)

Chromium Accumulation in Medicinal Plants Growing Naturally on Tannery Contaminated and Non-contaminated Soils - S. Jaison; T. Muthukumar (Biological Trace Element Research, 2017)

Characterisation of defatted Scenedesmus dimorphus algal biomass as animal feed - S. Vidyashankar; K. S. VenuGopal; V. S. Chauhan; S. P. Muthukumar; R. Sarada (Journal of Applied Phycology, 2015)

Biodegradation of malachite green by Ochrobactrum sp. - S. R. Vijayalakshmidevi; Karuppan Muthukumar (World Journal of Microbiology and Biotechnology, 2014)

Induction of systemic resistance by mixtures of antagonist bacteria for the management of crown rot complex on banana - G. Sangeetha; R. Thangavelu; S. Usha Rani; A. Muthukumar; R. Udayakumar (Acta Physiologiae Plantarum, 2010)

The demography of feral alfalfa (Medicago sativa L.) populations occurring in roadside habitats in Southern Manitoba, Canada: implications for novel trait confinement - Muthukumar V. Bagavathiannan; Robert H. Gulden; Graham S. Begg; Rene C. Van Acker (Environmental Science and Pollution Research, 2010)

Captive breeding and larval development of the scyllarine lobster Petrarctus rugosus - T.S. Kumar; M. Vijayakumaran; T. Senthil Murugan; Dilip Kumar Jha; G. Sreeraj; S. Muthukumar (New Zealand Journal of Marine and Freshwater Research, 2009)
The scyllarinid lobster, Petrarctus rugosus was reared to the postlarval nisto in 51 days at 24.9–26.5°C between November 2003 and April 2004 in Chennai, India. The lobster had eight phyllosomal instars. The eighth instars died while moulting to nisto. Instar VI was attained in 34 days with an average intermoult period of 5.4 days, whereas the last two moults took 17 days to complete. The captive breeders mated and bred several times between November and April with peak spawning in February. Repetitive breeding was observed with the brooding period varying from 11 to 17 days. Mean fecundity was 17 004 eggs ± 11 486 (SD). Hatching percentage was between 0.00 and 87.44.

Biodegradation of palmarosa oil (green oil) by Serratia marcescens - S. Mohanan; S. Maruthamuthu; N. Muthukumar; A. Rajasekar; N. Palaniswamy (International Journal of Environmental Science and Technology, 2007)

Microbiologically influenced corrosion in dairy effluent - B. Ramesh Babu; S. Maruthamuthu; A. Rajasekar; N. Muthukumar; N. Palaniswamy (International Journal of Environmental Science and Technology, 2006)